2021
DOI: 10.1371/journal.pone.0253277
|View full text |Cite
|
Sign up to set email alerts
|

Dogs fail to reciprocate the receipt of food from a human in a food-giving task

Abstract: Domestic dogs have been shown to reciprocate help received from conspecifics in food-giving tasks. However, it is not yet known whether dogs also reciprocate help received from humans. Here, we investigated whether dogs reciprocate the receipt of food from humans. In an experience phase, subjects encountered a helpful human who provided them with food by activating a food dispenser, and an unhelpful human who did not provide them with food. Subjects later had the opportunity to return food to each human type, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 105 publications
(150 reference statements)
1
9
2
Order By: Relevance
“…Although our finding that neither dogs nor wolves formed reputations of humans after direct experience is somewhat surprising given there is some evidence that wolves [37] and dogs [15][16][17][18]37] can form direct reputations, other studies have found that they could not [19,20]. Additionally, Jim et al [39] could not demonstrate that Asian elephants could form reputations of humans after direct experience and Subiaul et al [8] found that chimpanzees only learnt to discriminate between two humans after at least 32 trials, and one chimpanzee failed to show a consistent preference for a familiar generous partner.…”
Section: Plos Onecontrasting
confidence: 91%
See 1 more Smart Citation
“…Although our finding that neither dogs nor wolves formed reputations of humans after direct experience is somewhat surprising given there is some evidence that wolves [37] and dogs [15][16][17][18]37] can form direct reputations, other studies have found that they could not [19,20]. Additionally, Jim et al [39] could not demonstrate that Asian elephants could form reputations of humans after direct experience and Subiaul et al [8] found that chimpanzees only learnt to discriminate between two humans after at least 32 trials, and one chimpanzee failed to show a consistent preference for a familiar generous partner.…”
Section: Plos Onecontrasting
confidence: 91%
“…Moreover, two studies by Carballo et al [ 17 , 18 ] showed that dogs preferred to approach and gazed more at a generous human than a selfish one in a food-giving situation [ 17 ] and when confronted with an unsolvable task [ 18 ]. However, other studies have found that dogs could not form reputations of humans after direct experience–Piotti et al [ 19 ] could not demonstrate that dogs formed a reputation of an experimenter based on her skilfulness or the quality of the interaction and McGetrick et al [ 20 ] found that dogs did not prefer a helpful human, who provided them with food by activating a food dispenser, compared to an unhelpful human, who did not provide them with food, which suggests that they did not form reputations of the humans based on their cooperativeness.…”
Section: Introductionmentioning
confidence: 99%
“…This study was similar to experimental reciprocity studies carried out with dogs (Gfrerer & Taborsky, 2017, 2018McGetrick et al, 2021) and rats (Rutte & Taborsky, 2007, 2008. Initially, the dogs went through a training phase to learn how to use the apparatus and/or to become habituated to the test setup.…”
Section: General Overviewmentioning
confidence: 93%
“…Apart from the fact that one study employed pet dogs whereas the others focused on military dogs, one potential reason for different outcomes between these studies could be the species of the partner. McGetrick et al (2021) used humans as partners, whereas Taborsky (2017, 2018) employed dogs. Dogs have been shown to treat humans and conspecifics differently in experimental prosociality studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation